Florida Coonties and Atala Butterflies - Daniel F. Culbert (EDIS)
Revised! ENH117, a 10-page illustrated fact sheet by Daniel F. Culbert, describes this unusual native cycad — its habitat and range, description, non-landscape uses, landscape characteristics and uses, propagation and pest management — and the rare atala butterfly for which it is the sole host — legal status, management, and atala gardening. Includes references. Published by the UF Department of Environmental Horticulture, March 2010.